A Specific Case of Non-Specificity: Longitudinal Effects of Dysfunctional Attitudes on Depressive, Eating Disorder and Aggressive Symptoms in Children and Adolescents - Meiser, Susanne; Esser, Günter (Journal of Depression And Therapy, 2017)
An important step in the validation of disorder-specific etiological models is the examination of the predictive specificity of proposed vulnerability factors. It may advance the understanding of the emergence of comorbidity and the identification of at risk-populations for mental disorders. To enhance the currently limited evidence on the specificity of Beck´s cognitive diathesis-stress model of depression, the present study investigated longitudinal effects of dysfunctional attitudes and stressful life events on the development of depressive, eating disorder and aggressive symptoms in children and adolescents. A large sample of initially asymptomatic children and adolescents completed self-report symptom measures at study entrance and again approx. 20 months later, and reported stressful life events during the study interval. Stressful life events proved to be a risk factor to all investigated symptom domains. Dysfunctional attitudes at T1 were prospectively related to depressive symptoms, aggressive behavior and weight concerns at T2. However, types of associations varied as dysfunctional attitudes showed linear associations with weight concern, but nonlinear effects on depressive and aggressive symptomatology. Findings of the current study thus suggest that dysfunctional attitudes are not uniquely related to the development of depressive symptomatology in children and adolescents, but may contribute to adverse outcomes in various symptom domains. Thus, intervention efforts based on Beck´s vulnerability - stress model of depression may turn out to be useful in reducing vulnerability to a variety of outcomes in children and adolescents.
Keywords: Dysfunctional Attitudes; Specificity; Cognitive Vulnerability; Depression; Children and Adolescents; Eating Disorders; Aggressive Behavior; Nonlinear Effects